New perspectives on the roles of nanoscale surface topography in modulating intracellular signaling. Issue 1 (February 2021) - Zhang, Wei; Yang, Yang; Cui, Bianxiao
Highlights: A brief overview of cellular responses to extracelluar nanotopography. Ligand two-dimensional(2D) nanotopography affects cell-surface receptor signaling. 3D surface nanotopography induces cell membrane curvatures to regulate cellular processes. Current perspectives on the nanotopography-induced gene expression. Future challenges and directions to study the effects of nanotopography on cells.. Abstract: The physical properties of biomaterials, such as elasticity, stiffness, and surface nanotopography, are mechanical cues that regulate a broad spectrum of cell behaviors, including migration, differentiation, proliferation, and reprogramming. Among them, nanoscale surface topography, i.e., nanotopography, defines the nanoscale shape and spatial arrangement of surface elements, which directly interact with the cell membranes and stimulate changes in the cell signaling pathways. In biological systems, the effects of nanotopography are often entangled with those of other mechanical and biochemical factors. Precise engineering of 2D nanopatterns and 3D nanostructures with well-defined features has provided a powerful means to study the cellular responses to specific topographic features. In this Review, we discuss efforts in the last three years to understand how nanotopography affects membrane receptor activation, curvature-induced cell signaling, and stem cell differentiation.